PERANCANGAN APLIKASI VIDEO STREAMING UNTUK PEMANTAUAN AIR LAUT KETIKA TERJADI GEMPA - Irawan, Wahyu; Dermawan, Denny; Retnowati, Nurcahyani Dewi (Compiler, 2013)
The geographical position of Indonesia is located in an earthquake-prone area that is potentially most earthquake-tsunami, it takes a transmission medium to connect the cameramonitoring results between the sender and receiver of information or data that may provide information to the natural disasters. The transmission media can be a media streaming seawater and alarm monitoring that is connected with vibration sensor that functions as a medium for early warning of natural disasters. From the test results it can be concluded that the alarm system warning of earthquakes, able to work well as vibration sensor detects vibration. As well as video streaming process can run well on a LAN network using HTTP protocol 8080. Society as a client can access the video streaming server via the address specified by the application server.